Isaac Tolentino the first Filipino comicbook editor (1979)
The name Isaac Tolentino is perhaps unfamiliar in the world of comics, but since he helped edit and churn out the very first Philippine comic book ever made (Halakhak Komiks), he had quite an important role in Philippine comic book history. Though he most likely would have a lesser-known name among the legends of the early Filipino comic book industry, such as Francisco Coching, Mars Ravelo, and Tony Velasquez, Tolentino's contribution is no less significant. His career as an editorial cartoonist spanned over forty years, interrupted only by World War II and his brief involvement with *Halakhak Komiks* in the mid-1940s. Born in 1905 in Ermita, Manila, and educated in fine arts under the tutelage of renowned painter Fernando Amorsolo, Tolentino's influence in the arts, though understated, is undeniably significant in shaping the early landscape of Philippine comics.
Keywords: Comics books, strips, etc; Tolentino, Isaac